Implementaion of Pregnancy Exercises as an Effort to Accelerate Stunting Reduction in Bukittinggi City in 2023 - Putri, Diana; Ulsafitri, Yellyta; Pertiwi, Yessi (International Journal of Community Services, 2024)
Background: Stunting is a health problem that is of concern to the government in Indonesia.The incidence rate in West Sumatra Province from SSGI data (2022) was 25.2% and in Bukittinggi City it was 16.8%. One indirect cause of stunting is low birth weight. One of the specific nutritional intervention efforts for stunting is Antenatal Care (ANC). The ANC standard in Indonesia is 14 T, one of which is pregnancy exercise. Pregnancy exercise has the benefit of normal birth weight. ACOG explains that the benefits of exercise in pregnancy can reduce the incidence of low birth weight. so that pregnancy exercise can be implemented as an effort to accelerate stunting reduction. The aim of this activity is to increase knowledge about pregnancy exercise and mothers to be able to implement pregnancy exercise independently as a form of concern for pregnant women in reducing the incidence of stunting. This activity involves pregnant women in the second and third trimesters in Bukittinggi City. Methods: The method of implementing activities goes through 3 stages, namely preparation, implementation and evaluation stages. Result: Pregnant women who attended this activity were 85% of the target participants, all pregnant women were very enthusiastic about participating in pregnant women's exercise. Activities are carried out in 3 stages starting from the introduction stage, implementation of activities and evaluation in the form of a discussion session. Conclution: pregnant women get knowledge about the benefits of pregnancy exercise and to implement pregnancy exercise independently at home, each mother is given a pregnancy exercise guide in the form of a pregnancy exercise leaflet.